The Four Stages of Social Impacts among Ningxia China Students Studying in Malaysia - Zhang, Rui (Advances in Social Sciences Research Journal, 2022)
The study investigated the learning experiences and the adaptation process among China international students studying abroad in Malaysia. The paper aims to highlight how the four stages of shocks, adjustment, responses and outcomes affected significantly on their social life in a Malaysian setting. The study employed a qualitative paradigm where a total of ten participants were interviewed. A set of semi-structured questions was used during the interviews. Interviews were transcribed. Coding and constant comparison were adopted during data analysis. The findings show the sub-themes of culture shocks, the major adjustments such as assimilating of living habits, the overwhelmed responses as the students began to reaffirm their assumptions and the meaningful outcomes were a change in the world view which enabled them to function effectively. The results yielded from this study contributed significantly towards the knowledge of study abroad and internationalisation. Thus, this implies that to able to succeed while studying abroad, it is important to understand the comprehensive adaptation process caused by the four stages of social impacts among the students in a local setting.